2016
DOI: 10.1515/ijcre-2015-0215
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Validated CFD Model for Gas-Liquid Flow in a Round-Bottom Stirred Tank Equipped with Rushton Turbine

Abstract: Hydrodynamics of gas-liquid flow in a round-bottom stirred tank is modelled at two gas flow rates, constant bubble size and agitator speed of 300 rpm. A round-bottom tank equipped with four baffles and a Rushton turbine was chosen to represent a typical reactor used in hydrometallurgical processes operating under pressure. The applicability of different momentum interchange models and the Realizable k-ε, SST k-ω, and RSM turbulence models was studied using CFD software. The results were compared and validated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The model of Tomiyama et al [175] is also more sophisticated than the standard models and considers not only the turbulence but also the aspect ratio. Gradov et al [160], Basavarajappa & Miskovic [176], as well as Karimi et al [169] were able to demonstrate that the model of Lane et al [177] showed the best agreement with the experiments in turbulent flow. In addition, some models adjust the drag coefficient by swarm correction when particles are found in swarms [178].…”
Section: Drag Forcementioning
confidence: 96%
See 1 more Smart Citation
“…The model of Tomiyama et al [175] is also more sophisticated than the standard models and considers not only the turbulence but also the aspect ratio. Gradov et al [160], Basavarajappa & Miskovic [176], as well as Karimi et al [169] were able to demonstrate that the model of Lane et al [177] showed the best agreement with the experiments in turbulent flow. In addition, some models adjust the drag coefficient by swarm correction when particles are found in swarms [178].…”
Section: Drag Forcementioning
confidence: 96%
“…In the literature, the drag force is described as the interfacial force that has the most significant influence on the simulation [160,161]. The drag force is defined according to Eq.…”
Section: Drag Forcementioning
confidence: 99%
“…In the current work, it was decided to evaluate the suitability of the most frequently applied RANS models rather than attempt to implement a novel turbulence model by tuning the model constants for the hydrodynamics of the specific stirred tank. In our previous work [34], three popular models in the RANS family were tested, namely the Realizable k-ε model, the Shear Stress Transport k-ω model, and the Reynolds Stress Model (RSM). The Realizable k-ε model produce the most accurate results for single and multiphase mixing in round bottom STR.…”
Section: Suspended Solidsmentioning
confidence: 99%
“…Also, the effect of non-drag forces was found to be insignificant air-water mixing simulations. Therefore, in order to reduce computational complexity and promote solution stability the above mentioned combination of models was used to simulate drag force, while other forces models were ignored [34].…”
mentioning
confidence: 99%
“…The presence of heterogeneities can only be suspected from the calculation of mixing time and its comparison with the biological timescales. Alternatively, Computational Fluid Dynamics (CFD) is more and more used to predict the flow field and spatial distributions of reactants in various reactors and bioreactors (Haringa et al, 2018;Gradov et al, 2017;Morchain et al, 2014). Concerning the investigation of aerobic fermentations, the use of CFD is not outstretched yet due to the lack of physical models and appropriate validation; particularly for T. reesei cultures, the complex rheology makes the use of CFD even more questionable.…”
Section: Introductionmentioning
confidence: 99%